Temporal Change in Production and Consumption of Milk in the West Asian Countries - Abdul Wahid; S. K. Srivastava (The Indian Veterinary Journal, 2023)
The livestock sector plays a primary and budding role which providing a livelihood for a large part of poor people in the world and fairly contributes to the gross domestic product (GDP) of the country. The study examined the status of production and consumption of milk in different countries in the West Asia region from 2000 to 2017. Descriptive statistics as mean, percentage, etc., were used in the study. During this period milk production increased in all the countries of the region except Georgia, Iraq, and Bahrain wherein it reduced up to 28.89 percent. Turkey had lion’s share of more than 60 percent, in both production and consumption of milk in the region in the year 2017. Out of 18 countries, in the region per capita milk consumption reduced in the fifty per cent of countries with highest decline of about 55 percent in Qatar, while highest increase was reported by Armenia which was about 75 percent from the year 2000 to 2017. Per capita, milk consumption was more than 257 Kg/year in Armenia, while the lowest per capita milk consumption was in Yemen at 12 Kg/year in the year 2017.